Utilización del EM.1 (Microorganismo Eficaces) en el agua de beber, en pollos de engorde en fase de crecimiento y acabado en la ciudad de Babahoyo - Alcívar Junco, Willington Lelis (2012)
This research was conducted in the city of Babahoyo in the experimental farm of St. Paul's school of veterinary medicine faculty of agricultural sciences that is located at km 7/2 pathway to the Montalvo province of the rivers with an average temperature of 25.2 ° C, located 8msnm.cuya geographical location is 1 ° 46 'south latitude 97 ° "27 °" west latitude and average annual rainfall of 1800mm. Counted with duration of 42 days and used a total of 200 Hubbard broiler line Peterson, divided into 4 groups of the same age and each counted with 50 chickens, which acted as a treatment plot, and plot control experimental treatment respectively. The purpose of the proposed research was to evaluate the effect of orally administered product EM.1 in broiler chickens in the city of Babahoyo. We all work health, biological and food daily without significant developments in regard to serious problems or not solvable in a period of time that interferes with the final outcome of the investigation. It took the weight recorded weekly and daily food consumption values, water consumption, mortality and inverted values (production costs). The data were analyzed using completely randomized design; we determined that there was high statistical significance (P ≤ 0.05). Cumulative feed conversion in treatment 3 (2.06) was the best. Percent mortality was 2% for treatment 1, 2, 3 while for the control was 0%.